Development of Instruments and Formulas for Data Processing for Vocational Education Alignment - Kuat, Tri; Santosa, Budi; Susatya, Edhy; Sutrisno, Djoko; Purnawan, Purnawan; Budiastuti, Pramudita; Triatmaja, Adhy Kurnia; Mahmudah, Fitri Nur; Kurniawan, Arief; Prima, Rendra Ananta (Journal of Vocational Education Studies, 2024)
The very rapid development of DUDI demand quality unit education vocation. Especially on the relevance in accordance with DUDI needs. SMK as printer graduates who are ready Work need do effort alignment for increase absorption graduates. Research objectives This is explore alignment on units education vocational, developing instrument alignment education vocation, and make guidelines alignment education vocational. The method used in study This is a mixed method design with exploratory sequential design approach. The results of the study show that results research data analysis qualitative explore related to 12 categorizations and 40 coding. Development instrument alignment education vocation FGD results consist of of 7 components / dimensions and 23 items. Instrument has tested in a way reliable through proof validity and reliability. Results of the proof validity Contents the 7 (seven) experts were analyzed use index Aiken V average 0.89 > 0.8 which means own validity high. Proof second using EFA with KMO value 0.956 > 0.5 and CFA has good fit criteria X2, GFI, AGFI, CFI, TLI, CMIN/DF, and RMSEA values > cut of value. Measurement results alignment education vocation with use results development instrument the to 77 vocational schools and their DUDI partners that is show quadrant 2, meaning that SMK and DUDI have do alignment in accordance with indicator development instrument.